2002
DOI: 10.1080/15216540214534
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of Organic Anion Transporter 2 mRNA Expression by Nitric Oxide in Primary Cultured Rat Hepatocytes

Abstract: SummaryRole of nitric oxide (NO) 1 on the expression of organic anion transporter 2 (OAT2) located in sinusoidal domain of hepatocytes has been investigated. Effect of NO generated in vivo in rat and delivered in vitro to hepatocytes was determined. Lipopolysaccharide (LPS) and spermine NONOate (SPER/NO) were selected as the NO donors for in vivo and in vitro experiments, respectively. Constitutive basal expression of rOAT2 mRNA was detected in the normal rat liver and the level of its expression was decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The limited literature dealing with the effects of NO on the hepatic transporters suggests that the effect may be at the transcriptional level [17][18][19], altering mRNA of the transporters, or via a direct interaction with the transporters [21], altering their activities. Although the transcriptional/ translational level are normally associated with some delay in appearance, the direct interactions could potentially result in changes in the activity of the transporter in a much shorter time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The limited literature dealing with the effects of NO on the hepatic transporters suggests that the effect may be at the transcriptional level [17][18][19], altering mRNA of the transporters, or via a direct interaction with the transporters [21], altering their activities. Although the transcriptional/ translational level are normally associated with some delay in appearance, the direct interactions could potentially result in changes in the activity of the transporter in a much shorter time.…”
Section: Discussionmentioning
confidence: 97%
“…Recent in vivo and in vitro studies have suggested that NO may play an important role in the regulation of the expression or activity of various liver transporters [17][18][19][20][21]. Most of these studies [17,19,20] used bacterial lipopolysaccharide (LPS) to induce upregulation of NO release. However, LPS also increases the proinflammatory cytokines, which are also known to affect the hepatic influx and efflux transporters [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The condition for PCR was as follows; one cycle of 1 min at 948C, 35 cycles each for 30 s at 948C, 30 s at 558C and 90 s at 728C, and one cycle of 10 min at 728C. The PCR products (15 ml) were then separated in a 1% agarose gel electrophoresis and stained with ethidium bromide (20). The sets of primers used for PCR amplification are shown in Table 1.…”
Section: Total Rna Isolation and Rt-pcr Analysismentioning
confidence: 99%
“…hOCT1 and hOCT3 are both expressed in the sinusoidal membrane (blood side) of hepatocytes ( Fig. 2) and represent the first step in the hepatic excretion of many substances (12,15). In the kidney (Fig.…”
mentioning
confidence: 99%